Optical and structural properties of an Eu implanted Gallium Nitride quantum Dots/Aluminium Nitride Superlattice - Peres, M.
GaN/AIN structures made of GaN quantum dots (QDs) separated by AIN spacer layers, were doped with Europium by ion implantation. Rutherford Backscattering/Channelling measurements showed that Eu is incorporated mainly on near-substitutional cation sites within the superlattice region. Only slight deterioration of the crystal quality and no intermixing of the different layers are observed after implantation and annealing. After thermal annealing, photoluminescence associated with Eu3+ ions was observed. From its behaviour under different photon energy excitation and sample temperature we concluded that the Eu-related emitting centres are located inside the GaN QDs or dispersed in the GaN and AIN buffer or spacer layers. The 624 nm PL line, associated with Eu-doped GaN QDs, shows very low thermal quenching, suggesting recombination of confined carriers through rare-earth ion excitation.